Buenos Aires moderna : Fotografías de La Carpeta de los Diez - Pestarino, Julieta (2018)
The present article suggests working on some photographs taken in and about the city of Buenos Aires by certain members of the photography group La Carpeta de los Diez [The Folder of Ten], inquiring into the representation of the modern city and the resources used. The work will be done on photographs by Juan Di Sandro, Anatole Saderman and Annemarie Heinrich.